Two approaches to poverty: a comparative study on Amartya Sen's theory of capability deprivation and the framework of socil exclusion - Yuncu, Latife Demet. (Thesis (M.A.)-Bogazici University. Graduate Institute of Social Sciences, 2005., 2005)
All through history, different concepts have been employed to explain poverty. In contemporary debates about poverty, social exclusion and capability deprivation are two influential approaches. Both approaches highlight the multi-dimensional character of poverty, in other words they both underline that the deprivations involved in poverty cannot be sufficiently articulated only in economic terms; political and symbolic, cultural deprivations must be addressed as well.Motivated by Amartya Sen's contention that the social exclusion approach can be accommodated within the capability deprivation approach, the aim of this thesis is to present the different ways in which the two approaches problematize poverty and to reveal the different normative foundations that they implicitly embody. Some of the discrepancies are methodological, which are mainly about the nature and the constitution of the evaluative space in which poverty is assessed. Other discrepancies concern the normative underpinnings of the two theories. An interpretation of the social exclusion approach through T. H Marshall's "citizenship status" reveals that while a rights-based framework is necessarily the ground on which the social exclusion approach rests, this normative dimension is not a necessary component of the capability deprivation approach. This difference, I believe, is significant in establishing poverty as a political issue.
Keywords: Poverty.; Marginality, Social.; Citizenship.